Ultrasound of selected pathologies of the small intestine - Smereczyński, Andrzej (J Ultrason, 2013)
Intestines, especially the small bowel, are rarely subject to US assessment due to the presence of gases and chyme. The aim of this paper was to analyze ultrasound images in selected pathologies of the small intestine in adults, including the aspects of differential diagnosis. MATERIAL AND METHODS: In 2001–2012, abdominal ultrasound examinations were conducted in 176 patients with the following small bowel diseases: Crohn's disease (n=35), small bowel obstruction (n=35), yersiniosis (n=28), infectious diarrhea (n=26), bacterial overgrowth syndrome (n=25), coeliac disease (n=15) and small bowel ischemia (n=12). During examinations patients were fasting and no other particular preparations were needed. Convex transducers of 3.5–6 MHz and linear ones of 7–12 MHz were used. The assessment of the small intestine in four abdominal quadrants constituted an integral element of the examination. The following features of the small bowel ultrasound presentation were subject to analysis: thickness and perfusion of the walls, presence of thickened folds in the jejunum, reduction of their number, presence of fluid and gas contents in the intestine, its peristaltic activity, jejunization of the ileum and enteroenteric intussusception. Furthermore, the size of the mesenteric lymph nodes and the width of the superior mesenteric artery were determined and the peritoneal cavity was evaluated in terms of the presence of free fluid. RESULTS: Statistically significant differences were obtained between the thickness of the small intestine in Crohn's disease or in ischemic conditions and the thickness in the remaining analyzed pathological entities. Small bowel obstruction was manifested by the presence of distended loops due to gas and fluid as well as by severe peristaltic contractions occurring periodically. In the course of ischemic disease, the intestinal walls were thickened without the signs of increased perfusion and in the majority of cases intestinal stenosis was observed. Fluid in the intestine was detected in all patients with coeliac disease, gas in 86.7% of patients, thickening of the folds in the jejunum in 86.7%, their reduction in 80%, increased (enhanced) peristalsis in 93.3% and jejunization in 40%. In 80% of coeliac disease cases, the intestine showed the features of hyperemia on color Doppler examination and in 53.3% of patients the dilated lumen of the superior mesenteric artery was detected. Enlarged mesenteric lymph nodes were visualized in 73.3% of the subjects, enteroenteric intussusception in 33.3% and free fluid in the peritoneal cavity in 60%. CONCLUSIONS: 1. Small bowel obstruction is manifested by the presence of evidently dilated intestinal loops filled with gas and fluid and periodical severe deepened peristalsis. 2. Ischemic changes and Crohn's disease are characterized by the presence of fragmentarily thickened intestinal walls and intestinal stenosis. Moreover, in Crohn's disease, increased wall perfusion and mesenteric adenomegaly is encountered. 3. A. increased amount of fluid mainly in the jejunum, thickened and hyperemic jejunal walls, increased peristalsis; B. hypertrophied mucosal folds – often their number is reduced, jejunization and transient enteroenteric intussusception; C. ultrasound changes that require the differentiation with small intestinal bacterial overgrowth syndrome and, to a lesser degree, with infectious diarrhea.